The killing state : capital punishment in law, politics, and culture - Sarat, Austin (Oxford University Press, 2001)
Over 7,000 people have been legally executed in the United States this century, and over 3,000 men and women now sit on death rows across the country awaiting the same fate. Since the Supreme Court temporarily halted capital punishment in 1972, the death penalty has returned with a vengeance. Today, there appears to be a widespread public consensus in favor of capital punishment and considerable political momentum to ensure that those sentenced to death are actually executed. Yet, the death penalty remains troubling and controversial for many people. The "Killing State: Capital Punishment in Law, Politics, and Culture" explores what it means when the state kills and what it means for citizens to live in a killing state, helping us understand why America clings tenaciously to a punishment that has been abandoned by every other industrialized democracy. Edited by a leading figure in socio-legal studies, this book brings together the work of ten scholars, including recognized experts on the death penalty and noted scholars writing about it for the first time.; Focused more on theory than on advocacy, these bracing essays open up new questions for scholars and citizens: what is the relationship of the death penalty to the maintenance of political sovereignty? In what ways does the death penalty resemble and enable other forms of law's violence? How is capital punishment portrayed in popular culture? How does capital punishment express the new politics of crime, organize positions in the "culture war," and affect the structure of American values? This book is a timely examination of a vitally important topic: the impact of state killing on our law, our politics, and our cultural life